Gross biometrical and histomorphological changes in thymus and spleen of rabbit with age - Alboghobeish, Naeem (The Indian Journal of Animal Sciences, 2012)
Developmental studies of rabbit thymus from birth to one year of age showed that the average minimum weight( 190.8± 18.83mg) was at birth day and the maximum weight (3779±466.78mg) was at the age of 180 days. The weightincreased after 180 days, indicating all involution of thymus. The lobular area and distribution of the lymphatic cells alsoincreased up to 180 days and then decreased till 360 days. The arrangement of lymphatic cells in form of cord was seenat birthday. Cortical area as compared to medullary increased up to 180 days. Involution of thymus was observed at 270days age and its parenchyma was replaced by adipose tissue at 360 days of age. The number and size of thymic corpusclesincreased with age. Weight or spleen increased gradually from birthday (177.4± 13.13mg) to 360 days (1692±42.07mg)but significantly up to 180 days. The capsular connective tissue had less muscular cells. The number of white pulps/mm² decreased with age. The white pulp at birthday was like a small lymphoid follicle without periarteial lymphatic sheath (PALS). The PALS developed at 3 months. Red pulp and marginal zone also developed with age. The results show·that thymus of the rabbit develops significantly up to 180 days, and then involutes. The spleen showed enlargement and development from birth to one year, but this development was unrelated to the involution of thymus.